PANCASILA ECONOMIC CONCEPTS IN SHARI’AH ECONOMIC PERSPECTIVE - Misbahul Ali; Nurul Huda (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
Indonesia was a country that used the Pancasila economic system. The Pancasila economy was a joint effort based on kinship and national cooperation. In terms of religion, the majority of Indonesians were Muslim. Therefore, it was appropriate that the principles in the Pancasila economy were more inclined to the principles of shari’ah economics. Shari'ah economic principles were aimed at the welfare of the community. According to the researchers' assumptions, it was necessary to study that the implementation of the Pancasila financial system in Indonesia was still far from expectations. This study explored and analyzed the economic concept of Pancasila from the perspective of shari’ah economics to find a new formula that did not cause social inequality and can be applied to people's lives, especially in Indonesia. This type of research belongs to the kind of literature (library research), which was descriptive qualitative. The data analysis used in this study was a constant comparative analysis. It was more placed as a procedure for observing the results of data reduction or data processing to establish the reliability of building concepts, categories, generalizations overall research findings themselves so that they were correct. Completely coherent with the data and with the reality in the field. The study results showed that Pancasila Economy and Shari’ah Economics both prioritize the principle of kinship to create justice and welfare for the community.